The field researcher's handbook a guide to the art and science of professional fieldwork - Danelo, David J. (Georgetown University Press, 2017)
Field research, the collection of information outside of a lab or workplace setting, requires skills and knowledge that are not typically taught in the classroom. Fieldwork demands exploratory inquisitiveness, empathy to encourage interview subjects to trust the researcher, and sufficient aptitude to work professionally and return home safely. The Field Researcher's Handbook provides a practical guide to planning and executing fieldwork and presenting the results. David Danelo has written this book based on his experience conducting field research in over fifty countries as well as from teaching others a holistic approach to field research. His knowledge of how to be observant and operate safely in any environment was further enhanced by his time as a combat veteran in the US Marine Corps. This book introduces the skills that new researchers will need in the field, including anthropology, travel logistics planning, body language recognition, interview preparation, storytelling, network development, and situational awareness. Danelo also discusses ethical considerations and how to recognize personal biases. This handbook intended for researchers in a variety of academic disciplines but also government, think-tank, and private-sector researchers